Assessment of the determinants and economic benefits of adoption of improved sweetpotato varieties in Uganda - Feukeng, F.; Otieno, D.J.; Okello, J.J.; Rajendran, S. (2024)
Various efforts have been made in agricultural research in sub-Saharan Africa to improve productivity, access to markets and reduce household food insecurity. In the sweetpotato sector in Uganda, the government and its partners, notably the International Potato Center with financial support from the United Kingdom’s Department for International Development and the Bill and Melinda Gates Foundation, have been working to improve access to quality planting materials, access to knowledge and information related to potato production by farmers and other value chain actors. However, no empirical analysis has been done to understand the determinants of adoption of such varieties and their potential economic benefits to the Ugandan economy. This study addressed this gap by analyzing data from 942 smallholder farmers in Amuria district of Uganda using three approaches; probit model, endogenous switching regression and economic surplus model. The results showed that the farm size, soil fertility status, distance to the shopping centre, group membership and the number of adopters known by the farmer were key drivers of adoption of the improved sweetpotato varieties. Adoption positively affects farmer's yield and negatively affects the cost of production. The economic surplus estimates showed that adoption could generate between US$ 35.74 million to US$ 36 million for the Ugandan economy. In addition, adoption could lead to a reduction of poverty by 0.7% and 2.21% in Uganda as a whole and eastern Uganda, respectively. Based on these insights, the study recommends development of social capital by promoting farmer field schools, farmer groups and cooperatives. In addition, soil fertility management technologies and targeted support based on farmers' socio economic characteristics are necessary to increase adoption rate and improve welfare.